Die Verbreitung der mitteleuropäischen Arten der Simulium variegatum Gruppe (Diptera: Simuliidae). - Kúdela, Matúš (Contributions to Entomology = Beiträge zur Entomologie, 2006)
This paper describes the occurrence of Simulium argyreatum Meigen, 1838, Simulium maximum (Knoz, 1961), Simulium monticola Friederichs, 1920, Simulium variegatum Meigen, 1818 and the not described taxon S. sp. aff. monticola in general, and more detailed in the territory of Slovakia. S. variegatum, S. argyreatum und S. monticola have large areas differing in some details (e.g. occurrence in the British Islands, Skandinavien, Northafrica). S. maximum is restricted to the higher mountains in Central and Southern Europe; S. sp. aff. monticola is known only from Slovakia till now. S. variegatum and S. argyreatum are common in Slovakia; the formerly published wide occurrence of S. monticola has not been confirmed. Revised data shows, that S. maximum is more common, than suspected. S. argyreatum is widely distributed through all altitudes. S. variegatum prefers lower (200-800 m a.s.l.) and S. maximum higher altitudes (600-1000 m a.s.l.) than S. monticola and S. sp. aff. monticola (400-800 m a.s.l.). Keywords Simulium variegatum group, occurrence, Central Europe.